Effect of Feeding Earthworm Meal As an Alternative Protein Source Replacing Fish Meal on The Performance of White Pekin Ducks - SWAIN, BIJAYA KUMAR; P. K. Naik; C. K. Beura; D. Kumar; S.K.Sahoo; S. K. Mishra; S. K. Bhanja; R. Behera (Indian Journal of Animal Nutrition, 2026)
An experiment had been conducted to study impact of replacing fish meal with EWM on performance of White Pekin meat type ducks.  Total of 120 day old white pekin ducks (40-52g) have been randomly distributed to 3 equal groups (4 deep litter pens per group, 10 ducklings per pen). These were reared following standard management practices for a duration of 8 weeks. Earthworm meal (EWM) utilized in this investigation had been prepared from Eisenia foetida. The earthworms were grown using cow dung and mixture of duck litter and cow dung as biomass. The matured earthworms have been killed by dipping them in warm water (50-600C) and dried in hot air oven (50-600C for 72 h), ground to powder form and mixed in diet. Ducklings have been assigned to one of three treatments i.e. 1) Control without added EWM; 2) diet with 1 % EWM replacing fish meal;3) diet with 2 % EWM replacing fish meal.   The EWM contained 55.76 % protein. Body weight gain and FCR improved significantly (P